School Professional Needs to Support Student Mental Health During the COVID-19 Pandemic - Rusch, Amy; Rodriguez-Quintana, Natalie; Choi, Seo Youn; Lane, Annalise; Smith, Maureen; Koschmann, Elizabeth; Smith, Shawna N. (Frontiers in Education, 2021)
School closures due to COVID-19 left students in Michigan without physical access to school mental health care professionals (SMHPs) and supports typically available in schools. This report examines the needs of SMHPs across Michigan during the early months of the COVID-19 pandemic and how those needs informed programming and resources provided by a University of Michigan school mental health training and implementation program. In April 2020, a web-based survey asking about student and SMHP mental health was sent to 263 SMHPs who had previously participated in this program. 155 SMHPs (58.9%) responded. Nearly half of SMHPs reported their students’ most pressing needs were support for self-care, anxiety, depression, and traumatic stress. Some SMHPs also met screening criteria themselves for depression and/or anxiety. This survey provided an overview of SMHPs’ concerns early in the COVID-19 pandemic and drove development of new COVID-19-related resources designed to support SMHPs.